Analisis Kandungan Piroksikam dan Deksametason pada Jamu Pegal Linu yang Beredar di Lombok Timur - Hanifa, Ahdiani; Febriani, Yuyun; Gemantari, Baiq Maylinda (Sinteza, 2024)
In recent year 2020 and 2021 BPOM discovered aching herbs containing medicinal chemicals such as piroxicam and dexamethasone. The addition of piroxicam and dexamethasone to herbal rheumatic pain can cause dangerous side effects such as myopathy, impaired kidney function, edema, hypertension, and gastrointestinal bleeding. The aim of this study was to determine the presence and levels of piroxicam and dexamethasone in herbal aches and pains circulating in East Lombok. The qualitative and quatittaive analysis of piroxicam and dexamethasone used in this research. The qualitative analysis used test of drug class compounds to determine the presence or absence of piroxicam and dexamethasone with FeCl3 reagent to detect piroxicam and acetic anhydrous and sulfuric acid reagent to detect dexamethasone.  Therefore, using TLC (Thin Layer Chromatography) as confirmation of the presence or absence of piroxicam and dexamethasone also used in this study. Each positive sample in the TLC process has confirmed and searched for levels using UV-Visible Spectrophotometry as quantitave analysis. The data result have analyzed by   SPSS version 16 to show the signification data in each sample. The TLC analysis results showed 6 positive samples containing piroxicam and 5 positive samples containing dexamethasone. According to assay results, the piroxicam levels were 13,71 ppm, 13,74 ppm, 14, 49 ppm, 13,87 ppm, 13, 99 ppm resepectively. The results for dexamethasone levels were 25,20 ppm, 0,45 ppm, 2,20ppm respectively. So, this show that herbal rheumatic pain in east Lombok contained piroxicam and dexamethasone with diffrence level in each sample with signification value p<0,05.